Physicochemical Characterization and Bioactive Compound Profiling of Oil Palm Leaf (Elaeis guineensis Jacq.) Extract for Green Nutraceutical Effervescent Tablets - Hanif Ardhiansyah; Fisa Savanti; Meci Aryani Saputri; Khusnul Khairul Nisa (Universitas Negeri Semarang, 2026)
The valorisation of oil palm leaf (Elaeis guineensis Jacq.) agricultural waste into high-value nutraceutical products embodies circular economy principles within the world's largest palm oil producing nation. Oil palm leaves, currently discarded across 16.83 million hectares of Indonesian plantations, harbour diverse antioxidant, antimicrobial, and anti-inflammatory bioactive compounds. This study presents a comprehensive, multi-technique physicochemical and chemical characterisation of palm leaf ethanol extract and its optimal effervescent tablet formulation (F1, acid:base = 1:1) relevant to clean technology nutraceutical development. The palm leaf extract was characterised by X-Ray Diffraction (XRD) nanostructural analysis using the Debye-Scherrer equation, Fourier Transform Infrared Spectroscopy (FTIR), and Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant stability was assessed by the DPPH radical scavenging assay over four weeks (n = 3). XRD analysis revealed nanoparticulate crystal sizes of 58.91 nm (granules) and 56.38 nm (tablets), with predominantly amorphous phase morphology preserved through pharmaceutical processing. FTIR confirmed phenolic O–H stretching (3420 cm⁻¹), fatty acid C–H chains (2920, 2851 cm⁻¹), ester carbonyl (1740 cm⁻¹), and aromatic C=C (1633 cm⁻¹), validating chemical composition. GC-MS identified 25 peaks with 19 characterised compounds; dominant bioactives include n-hexadecanoic acid (11.80%), combined heneicosane peaks (31.14%), hexadecanoic acid 2-hydroxy ester (10.39%), and heptadecene-(8)-carbonic acid-(1) (10.15%), with documented antioxidant, antimicrobial, and antiproliferative activities. Formulation F1 maintained IC50 = 21.22 mg/L unchanged over four weeks. Pharmaceutical processing preserves the nanostructural integrity and bioactive composition of palm leaf extract. The research validates a clean technology circular economy pathway converting palm leaf waste—currently 91.5 million tonnes dry weight annually in Indonesia—into stable, bioavailability-enhanced nutraceutical ingredients.